Multiple treg suppressive modules and their adaptability - Wing, James B.; Sakaguchi, Shimon (Frontiers in Immunology, 2012)
Foxp3+ regulatory T-cells (Tregs) are a constitutively immunosuppressive cell type critical for the control of autoimmunity and inflammatory pathology. A range of mechanisms of Treg suppression have been identified and it has not always been clear how these different mechanisms interact in order to properly suppress autoimmunity and excessive inflammation. In recent years it has become clear that, while all Tregs seem to share some core suppressive mechanisms, they are also able to adapt to their surroundings in response to a variety of stimuli by homing to the sites of inflammation and exerting ancillary suppressive functions. In this review we discuss the relevance and possible modes of Treg adaptability and put forward a modular model of Treg suppressive function. Understanding this flexibility may hold the key to understanding the full spectrum of Treg suppressive behaviour.